2021
DOI: 10.1055/s-0041-1726309
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Size of Ulnar Styloid Fragment for the DRUJ Stability

Abstract: Background Ulnar styloid fractures can be associated with clinically significant instability of the distal radioulnar joint (DRUJ). However, the exact fragment size that results in DRUJ instability is unknown. Purpose The objective of this study was to determine the critical size of an ulnar styloid fracture that would result in a significant increase in DRUJ translation and forearm rotation. Methods Eight cadaveric specimens were used to investigate the effects of three different ulnar sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Specimens were tested in a custom system used also in prior studies (Maniglio et al, 2021a(Maniglio et al, , 2021b(Maniglio et al, , 2021c (Figures 1 and S1). The forearm was mounted using the PVC potting to position the humerus in a static, horizontal position.…”
Section: Testing Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…Specimens were tested in a custom system used also in prior studies (Maniglio et al, 2021a(Maniglio et al, , 2021b(Maniglio et al, , 2021c (Figures 1 and S1). The forearm was mounted using the PVC potting to position the humerus in a static, horizontal position.…”
Section: Testing Setupmentioning
confidence: 99%
“…Several recent studies have suggested that USFs have little influence on the patient-reported outcomes (Buijze and Ring, 2010; Kim et al., 2010; Souer et al., 2009), while other authors have reported an association with poorer outcome of wrist function with remaining DRUJ instability (Baradaran et al., 2017; May et al., 2002; Wysocki and Ruch, 2012). The importance of the fracture height has been discussed by many authors (Maniglio et al., 2021b; May et al., 2002; Pidgeon et al., 2018; Stoffelen et al., 1998) stating that only basal USFs may affect the outcome. Biomechanical studies have proved this concept and showed an increase in forearm rotation and dorsopalmar (DP) translation of the DRUJ (Maniglio et al., 2021b; Mirarchi et al., 2008; Pidgeon et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our model, we assumed that a perfect, fully repaired PQ achieved the same function as an intact PQ so that we used the same loading than in other biomechanical studies. 21 A poorer repair or partially repaired was simulated with half of this loading. After testing, all specimens were checked to ensure fractures were placed accurately.…”
Section: Measurementsmentioning
confidence: 99%